Desain Inverter Satu Fasa 400Watt dengan Kontrol Fuzzy Sugeno Berbasis Mikrokontroler Untuk Sistem Uninterruptible Power Supply - Nafi, Nasrul Annafi; Suryono; Wahjono, Endro (Jurnal ELEMENTER (Elektro dan Mesin Terapan), 2023)
At present, humanity's electricity needs are increasing and electricity is flowing directly from PLN which often experiences interruptions which causes power outages, the blackouts themselves are carried out because the load capacity exceeds the specified capacity. Therefore, it is necessary to seek alternative electrical energy as a substitute for extinguishing disturbances. Uninterruptible Power Supply (UPS) is used as an electronic device that can work in conditions where the PLN source is out. This study plans a UPS system that has a voltage sensor to detect blackouts. There is an SSR as a switch from the PLN power supply source to the UPS system. Single Phase Fullbridge Inverter in the UPS system is modulated by the Sinusoidal Pulse Width Modulation (SPWM) method with Fuzzy logic control. A single phase inverter using the SPWM switching technique can produce an output wave close to sine. Based on the results of the tests carried out, the UPS can work with a maximum power of 394.2W and the voltage is kept constant at 219V.